(untitled) (Journal of the College of Education for Women, 2019)
Phonetics has close relevance with Musicology; in this study I decided explaining the interlinkages and harmony between Phonetics and Musicology. Linguists preceded philosophers in an attempt to link Phonetics with Musicology; the 1st serious attempt to link Phonetics with Musicology was done by Ibn Jeny (Dead 392 IC), but the real attempt is found with Farabi through his book under title Al Musiqa Al Kabeer, he defined music and link it with tune and relation between melody and tone, This is the same as pointed out by Ikhwan Al Safa who followed the doctrine of al-Farabi, their attention was with music and link it with phoneme, as they made music independent science, and they created special mathematics rules for it. Melody in music cannot be studied in separately from toning; therefore we can find correlation between melody and toning in Phonetics, so it is impossible talking about the melody in the framework of the single tone, it is seen as part of a group ringtones, while toning can be talking about in the framework of the single word, therefore melody and toning can be in the something bigger, al-Farabi and Ikhwan Al Safa who pointed out to this point, but the rhythm is linked with phenomena above syllabic like accent, tuning, dedication, moreover explaining resonant phoneme in melody as its properties of phonetics, The phonic lesson of al-Farabi and Ikhwan Al Safa was musician lesson purely ٚ mixed with the phoneme and music elements together.